The Role of Service Quality in Increasing Tourist Satisfaction: A Case Study at Taman Mini Indonesia Indah Jakarta - Sari, Sukarni Novita (Technium Social Sciences Journal, 2021)
Abstract This study aims to answer questions about why there are many tourists complained regarding the services provided in TMII and how are the strategies to improve the quality of services so that tourists feel satisfied. This research is a qualitative research with a case study approach. Data was collected through semi-structured interviews and in a fluid atmosphere. In this study, interviews were conducted with 10 tourists, consisting of 8 domestic tourists and 2 tourists from the Netherlands. Interview was also conducted with an academic to obtain information on how changes should be made in terms of improving service quality with the aim of increasing tourist satisfaction. The result of this study shows that to improve the service quality of a tourist destination, the 5 elements must be considered namely reliability, responsiveness, assurance, empathy, and tangibles and to increase the tourist satisfaction, the following elements must be improved namely the facilities and infrastructure, activities or programs for tourists, convenience, shopping, entertainment, special events such as performing arts/festivals, cultural/ heritage, supporting factors, quality of service, accessibility of destinations and prices.